MAINSTREAMING ISLAMIC JURISTIC THOUGHT IN THE TEACHING OF HUMAN RIGHTS LAW: A CASE FOR INTEGRATIVE CURRICULUM AND PEDAGOGY IN AFRICAN LAW SCHOOLS - Dejo Olowu (Obiter, 2021)
Against the backdrop of the marked marginalization of Islamic juristic thought in human rights discourses and the consequential obscurity of possible synergy, this article proceeds from the premise that purposeful human rights education within a law degree programme leading to vocational careers must be all encompassing, able to respond to the demands of critical reasoning, and suitable for the analysis and understanding of global, regional and national challenges by local legal actors. In the African context, experience evokes an appeal for innovative approaches that not only prioritize integrative curricula but which also facilitate qualitative teaching methods that could guarantee the transfer of helpful skills and broad-based knowledge to boost the confidence of the learner in visualizing active future roles in human rights promotion and protection in whichever milieu he/she establishes a career. Highlighting the peculiar importance of Islamic Law in twenty-first century Africa, this article canvasses an approach that helps the law student to understand the practical realities that make Islamic Law a sine qua non for sound grasp of human rights law in his or her society while fully recognizing latent cultural, religious and other philosophical dilemmas and limitations to human rights as legal norms.